Recoding of the selenocysteine UGA codon by cysteine in the presence of a non-canonical tRNACys and elongation factor SelB. Issue 4 (4th May 2018) - Vargas-Rodriguez, Oscar; Englert, Markus; Merkuryev, Anna; Mukai, Takahito; Söll, Dieter
ABSTRACT: In many organisms, the UGA stop codon is recoded to insert selenocysteine (Sec) into proteins. Sec incorporation in bacteria is directed by an mRNA element, known as the Sec-insertion sequence (SECIS), located downstream of the Sec codon. Unlike other aminoacyl-tRNAs, Sec-tRNA Sec is delivered to the ribosome by a dedicated elongation factor, SelB. We recently identified a series of tRNA Sec -like tRNA genes distributed across Bacteria that also encode a canonical tRNA Sec . These tRNAs contain sequence elements generally recognized by cysteinyl-tRNA synthetase (CysRS). While some of these tRNAs contain a UCA Sec anticodon, most have a GCA Cys anticodon. tRNA Sec with GCA anticodons are known to recode UGA codons. Here we investigate the clostridial Desulfotomaculum nigrificans tRNA Sec -like tRNA Cys, and show that this tRNA is acylated by CysRS, recognized by SelB, and capable of UGA recoding with Cys in Escherichia coli . We named this non-canonical group of tRNA Cys as 'tRNA ReC ' (Recoding with Cys). We performed a comprehensive survey of tRNA ReC genes to establish their phylogenetic distribution, and found that, in a particular lineage of clostridial Pelotomaculum, the Cys identity elements of tRNA ReC had mutated. This novel tRNA, which contains a UCA anticodon, is capable of Sec incorporation in E. coli, albeit with lower efficiency relative to Pelotomaculum tRNA Sec . We renamed this unusual tRNA Sec derived from tRNA ReC as 'tRNA ReU ' (Recoding with Sec). Together, our results suggest that tRNA ReC and tRNA ReU may serve as safeguards in the production of selenoproteins and – to our knowledge – they provide the first example of programmed codon-anticodon mispairing in bacteria.